Empagliflozin alleviates type 2 diabetic renal fibrosis by inhibiting SLC7A7-mediated ferroptosis - Wendi Zhao; Guoxi Jin; Weihua Sun; Chenchen Wu; Qingqing Yang; Li Xue; Shandong Ye (Diabetology & Metabolic Syndrome)
Abstract Background Diabetic Kidney Disease (DKD) represents the most prevalent secondary kidney condition that progresses to end-stage renal disease globally. Empagliflozin (EMPA) effectively reduce blood glucose levels to mitigate the impact of DKD. Methods Researchers extracted kidney tissues from type 2 diabetic (T2DM) rats and performed transcriptome analysis to identify differential gene expression. Results The findings indicated a link to ferroptosis, closely associated with renal fibrosis. Subsequent cellular validation of T2DM and human renal proximal tubular (HK-2) cells under high-glucose conditions revealed that Collagen type I alpha 1 (COL1A1) and alpha -smooth muscle actin (α-SMA) levels increased in high-glucose group but decreased following EMPA treatment. These observations imply that EMPA mitigates renal fibrosis. Transcriptomic analysis revealed varied SLC7A7 expression in T2DM versus normal groups, and was verified by qPCR and WB. Significant changes in ferroptosis-related proteins, specifically acyl-CoA synthetase long-chain family member 4 (ACSL4) and glutathione peroxidase 4 (GPX4), emerged at the protein level. Further exploration revealed that EMPA suppressed ferroptosis by downregulation of SLC7A7 via the AMP-activated protein kinase/Glycogen synthase kinase 3 Beta/Nuclear factor erythroid 2-related factor 2 (AMPK/GSK-3β/NRF2) signaling pathway, thereby reducing renal fibrosis. Conclusions EMPA treatment could inhibit iron death to alleviate renal fibrosis, and the process was found to be related to the AMPK/GSK-3β/NRF2 pathway in subsequent mechanistic studies. EMPA is a proven treatment for diabetes. Understanding EMPA’s mechanism may uncover new drug targets and innovative therapies.